(untitled) (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2025)
Environmental health issues are a serious concern that cannot be ignored. The amount of accumulated waste continues to increase over time, in line with the expansion of human activities. According to data from the Ministry of the Environment in 2022, the total national waste stockpile reached 21.1 million tons, of which approximately 65.71% (13.9 million tons) was managed, while the remaining 34.29% (7.2 million tons) had not yet been optimally managed. To address this issue, Community Service Research (PKM) has been introduced as a solution to environmental health challenges, particularly waste management problems. The participatory action research method was used to analyze environmental health issues in Tambaklekok Village. Several stages of implementation were carried out, including: Data collection through observations and interviews, Implementation of Multiparty Deliberations or Focus Group Discussions (FGD), Training on Simple Household-Scale Composting, Conducting pre-tests and post-tests for training participants. The goal of this PKM initiative is to raise public awareness about environmental protection, provide references for effective waste management, and enhance environmental health knowledge and skills among the community in Tambaklekok Village. The results of the PKM program indicated a significant improvement in participants’ environmental health knowledge, with pre-test scores increasing from 4.85 to 9.69 in the post-test. This demonstrates that the PKM program, through Training on Simple Household-Scale Composting, has had a significant impact on enhancing knowledge and skills related to community environmental health in Tambaklekok Village. — Isu kesehatan lingkungan menjadi permasalahan serius yang tidak bisa dihindari. Jumlah timbunan sampah dari waktu ke waktu kian meningkat searah dengan perkembangan aktivitas yang dilakukan manusia. Berdasarkan data Kementerian Lingkungan Hidup pada tahun 2022 menyatakan bahwa jumlah timbunan sampah nasional mencapai 21,1 ton, sampah sekira 65,71% (13,9 juta ton) dapat terkelola, dan sisanya 34,295% (7,2 ton) belum terkelola dengan maksimal. Maka dari itu, penelitian berbasis Pengabdian Kepada Masyarakat (PKM) ini hadir sebagai solusi permasalahan kesehatan lingkungan terutama masalah sampah. Digunakan metode participatory action research untuk menganalisis isu kesehatan lingkungan di Desa Tambaklekok. Kemudian, dilakukan beberapa tahap pengabdian antara lain: (1) pengumpulan data melalui observasi dan wawancara, (2) pelaksanaan Musyawarah Multipihak atau Focus Group Discussion (FGD), (3) Pelatihan Pembuatan Kompos Sederhana, hingga (4) pelaksanaan pre-test dan post-test kepada partisipan pelatihan. Tujuan dilaksanakannya PKM ini adalah untuk memantik kesadaran masyarakat dalam menjaga lingkungan, memberi referensi pengolahan sampah secara efektif, dan meningkatkan pengetahuan serta keterampilan masyarakat akan pengolahan sampah demi peningkatan kesehatan lingkungan di Desa Tambaklekok. Dari PKM yang telah dilakukan, didapatkan hasil yang menunjukkan bahwa terdapat peningkatan pengetahuan kesehatan lingkungan partisipan dari nilai pre-test 4.85 menjadi 9.69 saat post-test. Dengan demikian, PKM melalui Pelatihan Pembuatan Kompos Sederhana Skala Rumah Tangga memiliki pengaruh signifikan dalam meningkatkan pengetahuan dan keterampilan terkait kesehatan lingkungan masyarakat di Desa Tambaklekok.